2020
DOI: 10.33737/gpps20-tc-143
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis on the Impact of Geometrical and Operational Variations on Turbine Hub Cavity Modes and Practical Methods to Control them

Abstract: This paper presents an experimental investigation on the impact of different design and operational variations on the instabilities induced at the hub cavity outlet of a turbine. The experiments were conducted at the "LISA" test facility at ETH Zurich. The axial gap at the 2 nd stage hub cavity exit was varied, and also three different flow deflectors were implemented at the cavity exit to control the cavity modes (CMs). Furthermore, the turbine pressure ratio was altered to mimic the off-design condition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This analysis, however, shows that they have a major impact on the main annulus gas ingestion. Hence, these results suggest that ingress in this axial turbine stage setup is not driven by the modes with the largest amplitudes of velocity or pressure fluctuations such that a tuning of the wheel space geometry as suggested by (Iranidokht et al, 2021) to reduce these mode amplitudes does not necessarily result in a better cooling effectivenss.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…This analysis, however, shows that they have a major impact on the main annulus gas ingestion. Hence, these results suggest that ingress in this axial turbine stage setup is not driven by the modes with the largest amplitudes of velocity or pressure fluctuations such that a tuning of the wheel space geometry as suggested by (Iranidokht et al, 2021) to reduce these mode amplitudes does not necessarily result in a better cooling effectivenss.…”
Section: Resultsmentioning
confidence: 77%
“…Outside this range, the fluctuations vanished abruptly. Recently, (Iranidokht et al, 2021) were able to affect the amplitudes and the frequencies of cavity modes observed on their test rig by modifying the wheel space geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the activity registered in the rim seal cavity generally did not appear in the inner rotor-stator cavity signal. Iranidokht et al (2020) reported experimental evidence of cavity modes and their sensitivities to turbine axial gap and turbine pressure ratio. An increased rotorstator axial gap is found to damp the peak amplitude of cavity modes by approximately a factor of seven.…”
mentioning
confidence: 99%